RESEARCH OF MODERN METHODS OF PROTECTION OF REINFORCED CONCRETE STRUCTURES FROM CORROSION - N. Saidova (International Engineering Journal For Research & Development, 2021)
This scientific article discusses the issue of the durability of concrete and reinforced concrete structures. The article describes the ways of using a basalt complex chemical additive (BKCD) as an increase in the corrosion resistance of road concretes that are operated in urban conditions.